(untitled) (Medical Forum Monthly, 2024)
Objective: To assess the causes and awareness of smoking in general population. Study Design: Observational / descriptive study Place and Duration of Study: This study was conducted at General Medicine OPD of PUMHS Hospital Nawabshah from 2015 up to January 2016. Materials and Methods: Two hundred patients were integrated in the study following receiving verbal well-versed consent. A self-administered questionnaire was filled and information was collected regarding reasons of smoking, and awareness regarding smoking that weather it is harmful, what is passive smoking etc. Results: When cases were interviewed regarding awareness of smoking than 121(60.5%) answered correctly that smoking is harmful for health while 79(39.5%) answered incorrectly. Passive smoking is risky for health, was answered correctly only by 76(38%) while 124(62%) persons did not knew that passive smoking very risky for health. Only 29(14.5%) cases answered correctly about smoking quitting centers in our country. 89(44.5%) peoples smoke to relieve occupational stress, 79(39.5%) participants smokes to relieve domestic stress, 67(33.5%) smoke for the digestive purpose, 111(55.5%) smokes when sitting with friends, 113(56.6%) smokes due to peer pressure and 78(39%) smokes due to habit from childhood and also their parents were smoker. Conclusion: This study showed that peoples had low level of consciousness regarding injurious consequences of smoking. Common reasons were seen peer pressure, reduce stress and digestive purpose.